2015
DOI: 10.1016/j.neuropsychologia.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of the primary somatosensory cortex: Opportunities for rehabilitation

Abstract: Emerging evidence indicates impairments in somatosensory function may be a major contributor to motor dysfunction associated with neurologic injury or disorders. However, the neuroanatomical substrates underlying the connection between aberrant sensory input and ineffective motor output are still under investigation. The primary somatosensory cortex (S1) plays a critical role in processing afferent somatosensory input and contributes to the integration of sensory and motor signals necessary for skilled movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
198
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(216 citation statements)
references
References 163 publications
(206 reference statements)
13
198
0
5
Order By: Relevance
“…The lower activation of brain regions known to constitute a response inhibition network together with better behavioral response inhibition performance suggests that response inhibition networks become more efficient when being triggered by the tactile modality. Interestingly the identified brain regions showing weaker activation in the tactile than in the visual condition, especially the SFG (BA6), have been shown to yield strong structural neuroanatomical connections to somatosensory association cortices [Borich et al, ; Fang et al, ]. It may be speculated that this structural neuroanatomical property is important for the effects observed in the SFG and MFG in the tactile experimental condition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lower activation of brain regions known to constitute a response inhibition network together with better behavioral response inhibition performance suggests that response inhibition networks become more efficient when being triggered by the tactile modality. Interestingly the identified brain regions showing weaker activation in the tactile than in the visual condition, especially the SFG (BA6), have been shown to yield strong structural neuroanatomical connections to somatosensory association cortices [Borich et al, ; Fang et al, ]. It may be speculated that this structural neuroanatomical property is important for the effects observed in the SFG and MFG in the tactile experimental condition.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the SMA and the superior frontal cortex show strong axonal connections to somatosensory associations cortices [Borich et al, ; Fang et al, ], which has also been shown in neuroanatomical studies in macaques [Luppino et al, ]. Furthermore, parietal somatosensory regions show strong connections to posterior parietal areas [Borich et al, ] which are important for sensory motor integration [Andersen and Buneo, ] and have recently been shown to be involved during response inhibition [Dippel et al, ]. Finally, changes in somatosensory functions have a direct effect on motor cortical areas and the control of responses [Borich et al, ].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Spasticity due to hyperexcitability of the stretch reflex can develop after stroke 35 , and its severity is correlated with the severity of motor impairments 36 . Motor impairments co-occur to varying degrees with impaired somatosensation 37,38 , which is associated with damage to ascending somatosensory pathways 39 .…”
Section: Compensatory Movement Strategiesmentioning
confidence: 99%
“…Motor output from the brain predominantly originates from the sensorimotor cortex, 258,259 and it was from the corticospinal tract that we saw an increase in FA, driven predominantly by changes in radial diffusivity. From the same dataset we previously reported changes in cortical thickness, fMRI maps, and TMS maps (Chapter 5).…”
Section: Sensorimotor Cortexmentioning
confidence: 82%